Unlocking the COP28 climate agenda in G10 economies: Do environmental taxes and environmentally-related technologies matter in the natural resource-load capacity factor connection? - Mohammed Musah; Isaac Ahakwa; Simplice A. Asongu; Michael Owusu-Akomeah; George Oppong Appiagyei Ampong (Sustainable Futures)
This study examines the role of environmental taxes and environmentally-related technologies in the link between natural resources and load capacity factor in G10 nations over the period 1994 to 2019. Using robust econometric techniques, the study reveals that natural resources damage environmental quality by mitigating the nations’ load capacity factor while environmental taxes and environmentally-related technologies promote sustainable environment by increasing load capacity factor. The relevance of environmental taxes and environmentally-related technologies in moderating the effect of natural resources on environmental quality is dampened by extant average levels of natural resources rents which are negative. Policy implications are discussed.